Development and course of chronic pain over 4 years in the general population: The HUNT pain study. (29th May 2018) - Landmark, T.; Dale, O.; Romundstad, P.; Woodhouse, A.; Kaasa, S.; Borchgrevink, P.C.
Abstract: Background: Epidemiological studies of chronic pain frequently report high prevalence estimates. However, there is little information about the development and natural course of chronic pain. Methods: We followed a random sample of participants from a population‐based study (HUNT 3) with annual measures over 4 years. Results: Among those without chronic pain at baseline, the probability of developing moderate to severe chronic pain (cumulative incidence) during the first year was 5%, a pain status that was maintained among 38% at the second follow‐up. The probability of developing chronic pain diminished substantially for those who maintained a status of no chronic pain over several years. Subjects with moderate to severe chronic pain at baseline had an 8% probability of recovery into no chronic pain, a status that was maintained for 52% on the second follow‐up. The probability of recovery diminished substantially as a status of chronic pain was prolonged for several years. Pain severity, widespread pain, pain catastrophizing, depression and sleep were significant predictors of future moderate to severe chronic pain, both among subjects with and without chronic pain at baseline. Conclusion: These findings suggest that the prognosis is fairly good after a new onset of chronic pain. When the pain has lasted for several years, the prognosis becomes poor. The same social and psychological factors predict new onset and the prognosis of chronic pain. Significance: The development and recovery of chronic pain is highly dependent on previous pain. The prognosis of chronic pain may be predicted well when considering its duration in combination with other clinical, social and psychological factors. Targeting modifiable prognostic factors may be particularly important for newly developed chronic pain.